PERENCANAAN EVALUASI PROGRAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH (MI) NURUL IHSAN KOTA JAMBI - Aris Munandar; Nia Firma Sari; Satirah Ad’ha; Nur Wulandari; Redi Apriansyah; Fitri Mutrikah; Nur Mutma’innah; Dewi Desmawati; El Fikri Purnama (Journal Publicuho, 2024)
This study discusses the planning of learning evaluation at Madrasah Ibtidaiyah (MI) Nurul Ihsan Jambi City. In the context of education, evaluation is an important process to improve the quality of learning and identify the needs for developing an education system. The main objective of this study is to see how the planning of learning evaluation is carried out at Madrasah Ibtidaiyah (MI) Nurul Ihsan Jambi City to increase the efficiency and effectiveness of the learning process. This study uses a descriptive qualitative approach. Data collection methods are carried out through observation, interviews, and documentation with three sources, namely: the principal, teachers, and school operators. As a result of the study, Madrasah Ibtidaiyah (MI) Nurul Ihsan Jambi City has tried to implement learning evaluations by standards, although there are still some problems in the administration, learning and implementation of the new curriculum, namely the independent curriculum. All stakeholders of Madrasah Ibtidaiyah (MI) Nurul Ihsan, Jambi City must be actively involved in achieving the goal of improving the quality of learning at Madrasah Ibtidaiyah (MI) Nurul Ihsan Jambi City.